NADPH Oxidase/ROS-Dependent VCAM-1 Induction on TNF-α-Challenged Human Cardiac Fibroblasts Enhances Monocyte Adhesion - Lin, Chih-Chung; Yang, Chien-Chung; Wang, Chen-Yu; Tseng, Hui-Ching; Pan, Chih-Shuo; Hsiao, Li-Der; Yang, Chuen-Mao (Frontiers in Pharmacology, 2016)
The inflammation-dependent adhesion molecule expressions are characterized in cardiovascular diseases and myocardial tissue infiltrations. Several pro-inflammatory cytokines are elevated in the acute myocardial injury and infarction. Tumor necrosis factor-α (TNF-α), a pro-inflammatory cytokine, is raised in the injury tissues and inflammatory regions and involved in the pathogenesis of cardiac injury, inflammation, and apoptosis. In fibroblasts, TNF-α-triggered expression of vascular cell adhesion molecule (VCAM)-1 aggravated the heart inflammation. However, the mechanisms underlying TNF-α-mediated VCAM-1 expression in cardiac fibroblasts remain unclear. Here, the primary cultured human cardiac fibroblasts (HCFs) were used to investigate the effects of TNF-α on VCAM-1 expression. The molecular evidence, including protein, mRNA and promoter analyses, indicated that TNF-α-induced VCAM-1 gene expression is mediated through the TNFR-dependent manner. Activation of TNF-α/TNFR system triggered PKCα-dependent NADPH oxidase (Nox)/reactive oxygen species (ROS) signal linking to MAPK cascades, and then led to activation of the transcription factor, AP-1. Moreover, the results of mRNA and promoter assay demonstrated that c-Jun/AP-1 phosphorylated by TNF-α turns on VCAM-1 gene expression. Subsequently, up-regulated VCAM-1 on the cell surface of TNF-α-challenged HCFs increased the number of monocytes adhering to these cells. These results indicated that in HCFs, activation of AP-1 by PKCα-dependent Nox/ROS/MAPKs cascades is required for TNF-α-induced VCAM-1 expression. To clarify the mechanisms of TNF-α-induced VCAM-1 expression in HCFs may provide therapeutic strategies for heart injury and inflammatory diseases.